Correlation Analysis between a Modified Ring Method and the FAST System. Issue 1 (March 2014) - Carrera-Gallissà, Enric; Capdevila, Xavier; Valldeperas, Josep
The original ring method and some of its modified versions were examined with a view to developing a straightforward, universal alternative for use by the textile industry. For this purpose, a total of 42 specimens of commercial woven fabrics differing in composition, weave type and aerial weight were studied by using the FAST method and a modified version of the ring method developed by the authors. Correlation between the results of the two methods was found to depend largely on (a) fabric formability, (b) bending rigidity, and (c) maximum extraction force and the time needed to reach it. Regression equations relating the main variables of the two methods via canonical correlations were developed. The proposed modified version of the ring method allows the easy, inexpensive determination of fabric formability, which was previously possible with the FAST method only.